Protective effects of sea cucumber surface-associated bacteria against Vibrio harveyi in brown-marbled grouper fingerlings - Mohamed Alipiah, Norfarrah; Ramli, Nur Hasli Syahidda; Low, Chen Fei; Nor Shamsudin, Mariana; Md. Yusoff, Fatimah (Inter Research, 2016)
Brown-marbled grouper Epinephelus fuscoguttatus (Forsskål) fingerlings are more vulnerable to diseases than the adult grouper because the fingerlings’ adaptive immune system is still in the development stage. The mortality rates are approximately 20 to 70% during outbreaks of vibriosis in aquacultures of grouper fingerlings. Studies were conducted to identify alternative treatments with low impacts on humans, animals and the environment as well as treatments that minimize the use of antibiotics in aquaculture. In this study, we report the first use of surfaceassociated bacteria isolated from marine invertebrates to increase fingerlings’ resistance against infections. Twenty-two surface-associated bacteria were isolated from the sea cucumber Stichopus badionotus and were identified with 16S rRNA gene sequencing. Three of the surfaceassociated bacteria had inhibitory activities against pathogenic Vibrio harveyi and V. parahaemolyticus. The fingerlings treated with the surface-associated bacteria Exiguobacterium acetylicum for 12 d prior to the challenge experiment with pathogenic V. harveyi showed sig - nificantly higher survival rates and increases in antibody titres compared to the control group. This study illustrats a symbiotic interaction between E. acetylicum and grouper fingerlings. E. acetylicum colonized the scales of grouper fingerlings and enhanced the fish’s immune response against the pathogen V. harveyi.